EXPLORING THE USE OF JIGSAW WRITING AMONG ESL WRITERS: A CLASSROOM RESEARCH - Noor Hanim Rahmat (University of Kuningan, 2015)
The use of jigsaw classroom has been used by Aronson (2015) since the 1970’s. It is a research based cooperative learning technique and has been successfully used in classrooms all over the world. Out of the jigsaw classroom, comes jigsaw writing and its serves the same function as cooperative learning in the classroom. The benefits of cooperative learning goes beyond learning the contents of the lessons, students gain a new way of learning in groups. Teachers teaching writing in the ESL classrooms will agree that teaching the writing process is not an easy task. ESL learners struggling with the learning of the language are faced with added difficulty of having to write essays in the ESL classroom. According to Elola (2010), collaborative writing can bring many benefits to learners in the ESL classroom. This study is based on the theories of Scaffolding and Cooperative learning. It introduces yet another interesting teaching method to make ESL writing a fun and interactive classroom activity. Qualitative and quantitative data analyzed revealed interesting implications for future teaching ESL writing.